Optimization of Fish Based Extruded Product by Twin Screw Extrusion using Response Surface Methodology and Shelf life Evaluation - Kamalakanth, C. K.; Joshy, C. G.; Varkey, Jones; Ravishankar, C. N.; Gopal, T. K. Srinivasa (Fishery Technology, 2025)
Effect of extrusion conditions like temperature,screw speed, and moisture content of the fishincorporated extruded snack on specific mechanicalenergy (SME) and texture were evaluated andoptimized by using response surface methodology.A central composite design with 20 runs wasformulated for the experiment and the quadraticmodel was most suitable for explaining the changesof dependent variables with respect to independentvariables. It was found that as the temperatureincreased, SME and texture decreased; whereas,SME was directly proportional with screw speed.There was a decrease in the SME and increase intexture as the moisture content increased. Maximumdesirability value of 0.873 revealed that thescrew speed of 380 rpm at a temperature of 140°Cand 17% moisture content were optimum for thedevelopment of fish incorporated extruded snackand values for SME and texture were251.26 KJ kg-1 and 9.86 N, respectively. Storage studyof fish-incorporated extruded snack developed atoptimized conditions revealed that thiobarbituricacid and texture were increased with storage period.Similarly, redness of the sample increased whilewhiteness and yellowness of the sample weredecreased with storage. At ambient temperature(28±1°C), the product had a shelf life of 4 months.